#1**0 **

2x + 6y = 66

8x - y = 39

x = (66 -6y) / 2

8x - y = 39

x = 6 * (11 - y) / 2

8x - y = 39

x = 3 * (11 - y)

8x - y = 39

x = 3 * (11 - y)

8*(3 * (11 - y)) - y = 39

x = 3 * (11 - y)

264 - 24y - y = 39

x = 3 * (11 - y)

- 25y = 39 - 264

x = 3 * (11 - y)

- 25y = -225

x = 3 * (11 - y)

y = 9

y = 9

x = 3 * (11 -9) =6

8x - y = 39

x = (66 -6y) / 2

8x - y = 39

x = 6 * (11 - y) / 2

8x - y = 39

x = 3 * (11 - y)

8x - y = 39

x = 3 * (11 - y)

8*(3 * (11 - y)) - y = 39

x = 3 * (11 - y)

264 - 24y - y = 39

x = 3 * (11 - y)

- 25y = 39 - 264

x = 3 * (11 - y)

- 25y = -225

x = 3 * (11 - y)

y = 9

y = 9

x = 3 * (11 -9) =6

Guest Feb 15, 2012